Efek Temperatur Pembakaran Biochar Kayu Putih (Eucalyptus alba) dan Frekuensi Penyiraman Kompos Teh terhadap Pertumbuhan dan Hasil Selada Darat (Lactuca saiva L.) Pada Tanah Vertisol - Aplonia Mau (Fakultas Pertanian, Universitas Timor, 2021)
Soil type in dry land, dominated by vertisol soil. Vertisol soil is a soil with a high klein content and has the characteristic of expanding and contracting periodically, which expands when wet and contracts when dry. Due to the nature of the soil, it is necessary to use soil amendments to increase soil aggregation and aeration so that the absorption of water in the subsurface layer of the vertisol soil is maximized. Shallow and fine lettuce roots require better aggregation and aeration of vertisol soil. This study aims to determine the effect of burning temperature for kayu putih (eucalypus alba) biochar and the frequency of giving compost tea on the growth and yield of lettuce (Lactuca sativa L.) on vertisol soil. This research is a field experiment carried out from March to May 2019 in the experimental garden of the Faculty of Agriculture, University of Timor, Kota Kefamenanu District, Sasi Village, Timor Tengah Utara Regency. This study uses a completely randomized design (CRD) with 2 factorials with the first factor being the combustion temperature of the biochar raw material which consists of 3 levels, namely 350ºC, 450ºC and 550ºC. The second factor is the frequency of watering of tea compost which consists of no compost tea, one watering a week, 2 watering a week and 3 watering a week. So that in this study there were 12 experimental units which were repeated 5 times. The results showed that the combination of biochar combustion temperature treatment and watering frequency of tea compost significantly affected the observation of plant height at 35 days after planting, number of leaves at 35 days after planting, and total plant fresh weight. Kayu putih (eucalypus alba) biochar which was charred at 350ºC gave the best effect on the growth and yield of lettuce. The frequency of watering compost tea once a week gave the best results on the growth and yield of lettuce (Lactuca sativa L.).